'Archives of Feeling': the AIDS Crisis in Britain 1987. Issue 1 (29th March 2017) - Cook, Matt
Abstract: This piece is an extended version of my inaugural lecture of the same title delivered on World AIDS day 2016 at Birkbeck College, University of London. It traces the emotional landscape of Britain at a key turning point in the history of AIDS in the UK. Drawing on a range of testimonial and other archives it explores the feelings at stake in the epidemic, how they related to press and politics, how they shaped everyday lives, and how they played out for those involved most directly with the escalating crisis. I argue that such 'archives of feeling' are fundamental to our understanding of intersecting social and intimate lives – past and present.